Design Improvement of Three Phase 12Slot-14Pole Outer Rotor Field Excitation Flux Switching Motor - S.M.N.S. Othman; M.Z. Ahmad; J.A. Rahim; F.S. Bahrim; E. Sulaiman (Institute of Advanced Engineering and Science, 2017)
This paper present with design improvement of 12Slot-14Pole outer rotor field excitation flux switching motor (ORFEFSM) from the initial design by implement Deterministic Optimization Method (DOM) which involve 2-dimensional Finite-Element Analysis (FEA). The design improvement starts with the non-active part, rotor and followed with active part, stator which involve the armature coil slot and field excitation coil (FEC) slot. Since it is one of local optimization method, this method involves more than one cycle of improvement depends on the design structure and slot-pole configuration until achieve optimum performance. However, the initial torque and power output of 12Slot-14Pole is 112.95 Nm and 50.46 kW. The main objective is to improve the structure in order to obtain optimum torque and power output. Besides, it is necessary to reduce flux saturation and optimize the flux flow between the rotor teeth and stator arc width. The target torque and power output performance is expected higher than 210 Nm and 123 kW. With the deterministic optimization method technique, the final torque and power output achived are 221.83 Nm and 189kW.